2021
DOI: 10.1007/s10792-021-02038-y
|View full text |Cite
|
Sign up to set email alerts
|

Tasquinimod efficacy and S100A9 expression in glucose-treated HREC cells

Abstract: Purpose Diabetic retinopathy (DR) is one of the leading causes of blindness in working-aged people. Few studies were on the relationship between S100 Calcium Binding Protein A9 (S100A9) protein and DR, and none on endothelial cells induced by tasquinimod in high glucose. Therefore, we assessed the relationship between tasquinimod and S100A9 in DR. Methods DR pathogenesis was simulated using high-glucose-induced human retinal endothelial cells (HRECs) to study the mRNA expression of s100a9, thrombospondin-1 (ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Interestingly, in the literature, there is a high variability in both experimental settings and results regarding the status of HREC/endothelial cells under high glucose concentrations (≥25 mM). In agreement with our data, other in vitro studies showed no relevant changes at 24 h [ 34 , 35 ]; however, at the same time of exposure, Jin et al [ 36 ] recently reported that 30 mM glucose in HREC induces proliferation (about +20%). These discrepancies in both the acute and chronic hyper-glucose-induced effects may be related to different experimental settings among laboratories, including the source and passage of HREC and the method used to assess cell survival, with the majority of in vitro studies performing the MTT assay.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, in the literature, there is a high variability in both experimental settings and results regarding the status of HREC/endothelial cells under high glucose concentrations (≥25 mM). In agreement with our data, other in vitro studies showed no relevant changes at 24 h [ 34 , 35 ]; however, at the same time of exposure, Jin et al [ 36 ] recently reported that 30 mM glucose in HREC induces proliferation (about +20%). These discrepancies in both the acute and chronic hyper-glucose-induced effects may be related to different experimental settings among laboratories, including the source and passage of HREC and the method used to assess cell survival, with the majority of in vitro studies performing the MTT assay.…”
Section: Discussionsupporting
confidence: 93%
“…In vitro studies report that endothelial cells are susceptible to high-glucose concentrations, although with notable differences among laboratories [ 34 , 35 , 36 , 37 , 38 ]. Before evaluating potential cytoprotective effects of DMF treatment in HREC cells under high glucose conditions, we first performed experiments to select the best time of exposure and concentrations of glucose leading to a significant cell viability impairment in HREC.…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacological activity of taquinmod is more associated with anti-vascular and anti-prostate cancer effects (Isaacs et al, 2006;Olsson et al, 2010;Boros and Vécsei, 2020). In the pathological environment of high glucose, taquinmod inhibits proliferation, migration and lumen formation of human retinal endothelial cells (Jin et al, 2022). Ribavirin, as an antiviral drug, is considered as a potential candidate for the treatment of HFMD (Leung et al, 2022).…”
Section: Discussionmentioning
confidence: 99%